An innovative single‐base extension method for synchronous detection of point mutations and MSI status in colorectal cancer. (30th December 2022) - Liang, Li; Li, Xin; Nong, Lin; Cai, Weijing; Zhang, Jixin; Liu, Ping; Li, Ting
Abstract: Background: An accurate genotyping analysis is one of the critical prerequisites for patients with colorectal cancer receiving matched therapies. Conventional genotyping analysis is currently used to detect either gene mutations or MSI status, delaying the detection of critical tumor biomarkers and thus the optimal time for treatment. An assay that analyzes both biomarkers in a streamlined process is eagerly needed. Methods: We developed an assay combining Multiplex PCR Amplification, Single‐base Extension and capillary electrophoresis (CE) analysis (MASE‐CE) for synchronous detection of KRAS / NRAS / BRAF mutations and MSI status. In a 190 colorectal cancer cohort, we identified seven somatic mutations in KRAS, NRAS and BRAF as well as five MSI loci (D2S123/D5S346/D17S250/BAT‐25/BAT‐26) simultaneously. KRAS / NRAS / BRAF mutations were detected by NGS and MASE‐CE, and MSI status were detected by PCR‐CE and MASE‐CE methods. Results: The MASE‐CE method showed high consistency with NGS for mutation detection (Kappa value ≥0.8) and PCR‐CE (Kappa value = 0.79). In addition, the limits of detection (LOD) of MASE‐CE assay for MSI and somatic mutation were 5% and 2%, respectively. Conclusions: In somatic mutation detection and MSI detection, the LOD of MASE‐CE assay was superior to that of qPCR and NGS. MASE‐CE assay is a highly sensitive, time‐saving and specimen‐saving method, which can greatly avoid the cumbersome testing process and provide clinical decision for doctors in time. Abstract : An accurate genotyping analysis is one of the critical prerequisites for patients with colorectal cancer receiving matched therapies. We developed an assay combining multiplex amplification with single‐base extension assays for synchronous detection of KRAS/NRAS/BRAF mutations and MSI status. In somatic mutation detection and MSI detection, the LOD of MASE‐CE assay is superior to that of qPCR and NGS.